Auditory Hallucinations: An Audiological Horizon? - Musiek, Frank E.; Morris, Sarah; Ichiba, Kayla; Clark, Liza; Davidson, Alyssa J. (Journal of the American Academy of Audiology, 2021)
Background Interesting data and theories have emerged regarding auditory hallucinations (AHs) in patients with schizophrenia. The possibility that these patients may have changes in the anatomy of the auditory cortex and/or subcortical structures of the central auditory nervous system and present with deficits on audiological tests is important information to the audiology community. However, it seems clear that, in general, audiologists are not sufficiently aware of these findings.Purpose There are two main purposes of this article: (1) to educate audiologists about AHs related to schizophrenia and related issues, and (2) to encourage audiologists and hearing scientists to become involved in the evaluation and research of AHs. This fascinating disorder is one in which audiologists/hearing scientists are well suited to make a significant contribution.Research Design A review and synthesis of the literature was conducted. Relevant literature was identified through PubMed, Google Scholar, as well as independent book chapters and article searches. Keywords driving the searches were AHs, auditory illusions, verbal and musical hallucinations, schizophrenia, and central auditory disorders. Given the currency of the topic, the information collected was primarily between 1990 and 2020.Study Sample The review is organized around categorization, prevalence, models, mechanisms, anatomy, pathophysiology, and audiological correlates related to AHs.Data Collection and Analysis Searches were conducted using well-known search engines and manual searches by each author. This information on AHs was then analyzed collectively by the authors for useful background and relevance, as well as important for the field of audiology.Results Several anatomical, physiological, and functional imaging studies have shown compromise of the auditory cortex in those with schizophrenia and AHs. Potentially related to this, are studies that demonstrated sub-par performance on behavioral audiologic measures for this unique clinical population. These findings align well with the kind of hearing disorder for which audiologists are well-trained to make significant contributions.Conclusion Neurobiological and audiological evidence is accumulating on patients with schizophrenia and AH potentially rendering it as both an auditory and psychiatric disorder. Audiologists should consider expanding their horizon and playing a role in the clinical investigation of this disorder.
Keywords: auditory hallucination; auditory illusion; verbal hallucination; musical hallucination; schizophrenia; central auditory disorder